Single crystal growth, electronic structure and optical properties of Cs2HgBr4. (October 2015) - Lavrentyev, A.A.; Gabrelian, B.V.; Vu, V.T.; Shkumat, P.N.; Parasyuk, O.V.; Fedorchuk, A.O.; Khyzhun, O.Y.
Abstract: We report on successful synthesis of high-quality single crystal of cesium mercury tetrabromide, Cs2 HgBr4, by using the vertical Bridgman–Stockbarger method as well as on studies of its electronic structure. For the Cs2 HgBr4 crystal, we have recorded X-ray photoelectron spectra for both pristine and Ar + ion-bombarded surfaces. Our data indicate that the Cs2 HgBr4 single crystal surface is rather sensitive with respect to Ar + ion-bombardment. In particular, such a treatment of the Cs2 HgBr4 single crystal surface alters its elemental stoichiometry. To explore peculiarities of the energy distribution of total and partial densities of states within the valence band and the conduction band of Cs2 HgBr4, we have made band-structure calculations based on density functional theory (DFT) employing the augmented plane wave+local orbitals (APW+lo) method as incorporated in the WIEN2k package. The APW+lo calculations allow for concluding that the Br 4p states make the major contributions in the upper portion of the valence band, while its lower portion is dominated by contributors of the Hg 5d and Cs 5p states. Further, the main contributors to the bottom of the conduction band of Cs2 HgBr4 are the unoccupied Br p and Hg s states. In addition, main optical characteristics of Cs2 HgBr4 such as dispersion of the absorption coefficient, real and imaginary parts of dielectric function, electron energy-loss spectrum, refractive index, extinction coefficient and optical reflectivity have been explored from the first-principles band-structure calculations. Graphical abstract: Highlights: Cs2 HgBr4 single crystal has been grown by Bridgman-Stockbarger method. Electronic structure of Cs2 HgBr4 single crystal is studied by XPS. XPS data reveal low hygroscopicity of Cs2 HgBr4 surface. First-principles calculations of total and partial densities of states are reported. Main optical characteristics of Cs2 HgBr4 are calculated.